Switching loss contributions of synchronous rectifiers in VRM applications - Dürbaum, Thomas; et al. (PESC Record - IEEE Annual Power Electronics Specialists Conference, 2003)
For the Synchronous Buck converter used in VRM applications, one major contributor to switching losses is reverse recovery. These losses however cannot directly be measured because capacitive current and several other phenomena superimpose the mere reverse recovery. The paper describes how to calculate the capacitive part of the drain current and how to de-embed the channel current out of the total drain current. This can show the size of Q rr and reveal effects such as gate bouncing and avalanche breakdown.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.lselek.switch
Keywords: Capacitive current; De-embedding; Gate bouncing; Half-bridge; MOSFET characterisation; Reverse recovery; Switching behaviour; Synchronous rectification; VRM